A framework for using autonomous adaptation as a leverage point in sustainable climate adaptation - H.M. Tuihedur Rahman (Elsevier, 2021)
Planned adaptations are commonly adopted by governments considering large-scale socio-economic and political interventions, while local communities innovate their adaptive responses using locally available resources – also known as autonomous adaptation. Congruence between planned and autonomous adaptation is needed to develop a concerted and effective effort to minimize the negative impacts of context-specific vulnerability. This paper offers a systematic framework for building congruence between planned and autonomous adaptation using a six-step approach to guide their integration while maintaining an environment for future autonomous innovations. We applied this framework to previously conducted case studies in Spain, Bangladesh and Canada, revealing key lessons for using autonomous adaptation as leverage points for sustainable climate adaptation.